Chemical composition and broiler meat quality when using melanin - N. V. Bogolyubova; R. V. Nekrasov; A. A. Zelenchenkova; N. S. Kolesnik; P. D. Lahonin; R. A. Rykov; J. A. Bogolyubova (Теория и практика переработки мяса)
The research was carried out to study an effect of the antioxidant melanin in the broiler nutrition on the chemical composition, antioxidant and technological properties of meat, and the fatty acid composition of abdominal fat. The experiment was conducted in the conditions of the physiological courtyard of the L. K. Ernst Federal Research Center for Animal Husbandry in 2023. Broilers (n = 27, N = 54) of the domestic broiler cross “Smena-9” were divided into two groups (control and experimental). Broilers of the control group were fed the basic diet, birds of the experimental group received the basic diet with the addition of water-soluble melanin at a dose of 1.42 mg /kg of bird weight from the 7th to 45th day of age. At the age of 45 days, the birds were slaughtered and the meat chemical composition, fatty acid content, and quality characteristics were determined. The addition of melanin to the diet led to an increase in the meat antioxidants in the breast by 18.75% (p < 0.0001) and in the thigh by 5.6%, and also resulted in an increase in reduced glutathione by 20.25%, glutathione peroxidase by 10.43%, catalase 17.35% in the breast compared with the control. The use of melanin in broiler diets contributed to an increase in the content of erucic and 8,11,14-eicosatrienoic acids in abdominal fat compared with the control (at p = 0.02 and p = 0.07, respectively), as well as to an increase in the moisture content in muscles and the enrichment of meat with the antioxidant.